Effects of Protective Resin Coating on the Surface Roughness and Color Stability of Resin-Based Restorative Materials - Bora Bagis; Tamer Tüzüner; Sedanur Turgut; Fatih Mehmet Korkmaz; Özgül Baygın; Yıldırım Hakan Bağış (The Scientific World Journal)
The aim of this study was to evaluate the effects of nanofilled protective resin coating (RC) on the surface roughness (Ra) and color stability (ΔE) of resin-based restorative materials (RM) (compomer (C), nanofilled composite (NF), and microhybrid composite (MH)) after being submitted to the ultraviolet aging (UV) method. Thirty-six specimens were prepared (n=6 for each group). The Ra and (ΔE) values and SEM images were obtained before and after UV. Significant interactions were found among the RM-RC-UV procedures for Ra (P<0.001). After the specimens were submitted to UV, the Ra values were significantly increased, regardless of the RC procedure (with RC; P<0.01 for all, without RC; C (P<0.01), NF (P<0.001), and MH (P<0.001)) for each RM. Significant interactions were found between the RM-RC (P<0.001) procedures for the ΔE values. The ΔE values were increased in each group after applying the RC procedures (P<0.001). Protective RC usage for RM could result in material-related differences in Ra and ΔE as with used UV method.